Linguistic, cultural and social considerations in the preparation of English language teaching programs in Guyana - Edwards, Walter F.
This paper reports on the results of a study on the linguistic organization of Standard English in Guyana. The research focused on the lexical, morphological, and syntactic systems of Standard Guyanese English as contrasted with Standard British English. The study identified problems faced by educators in preparing English teaching programmes for Guyanese children, which include identification of similarities and differences between Standard Guyanese English and the vernacular varieties of English spoken. It is suggested that teachers of English should take into serious consideration the linguistic properties inherent in these non-standard varieties
Keywords: Language education